Studi Eksperimen Pengujian Kebulatan Produk Hasil Pembubutan Pada Mesin Bemato - Estu, Panji; Erwansyah, Erwansyah; S Suzen, Zaldy (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The machining process in product manufacturing must meet several important criteria, including the product's outcome, accuracy, precision, quality, and quantity. Machine tools that have been used for a long period tend to experience a decline in performance, which can affect the machine's ability to produce products with the required quality, standard, or tolerance. The aim of this study is to evaluate the performance of a lathe machine that has been in use for approximately 10 years. As the machine ages, its performance may decrease, and optimal machine performance significantly influences the machining results. Therefore, an experiment was conducted to test the roundness deviation of the products produced through turning, by varying the spindle speed and depth of cut parameters, while keeping the feed rate constant. This study uses an experimental method to test and analyze machine performance based on the measurement of roundness deviations of the products. The material used was ST-41 steel with a diameter of Ø30 x 110 mm, and the cutting tool used was a Carbide Insert WNMG080404-TSF T9225G. Data on roundness was collected from products produced using the Bemato Series 44378 lathe machine with 9 test samples. Based on the test results, the highest roundness deviation found in BU 27 was 0.088 mm